Nickel and Scandium-Bearing Minerals Associated with Limonitic Laterite Zone of the Lameruru Deposit in Southeast Sulawesi, Indonesia - Supit, Jance Mudjani; Idrus, Arifudin; Petrus, Himawan Tri Bayu Murti; Sukadana, I Gde; Pratiwi, Fadiah (Indonesian Journal on Geoscience, 2025)
This study investigates nickel and scandium enrichment within a laterite profile developed on ultramafic rocks in the Lameruru area, Southeast Sulawesi. Utilizing mineralogical and geochemical analyses, the research examines transformations from parent rock through four laterite horizons: rocky saprolite, earthy saprolite, yellow limonite, and red limonite. Results reveal distinct enrichment patterns for Ni and Sc. Nickel is concentrated in the saprolite, hosted by minerals such as willemseite, vermiculite, lizardite, and antigorite, and decreases towards the red limonite, suggesting an initial enrichment during weathering followed by remobilization. Conversely, Sc increases throughout the profile, peaking in the red limonite and dominantly associated with goethite. Nickel is structurally bound within mineral lattices, while scandium is adsorbed onto mineral surfaces, particularly goethite in the red limonite. This contrasting behaviour highlights different geochemical controls influencing Ni and Sc enrichment during lateritization. Further research should explore these mechanisms to optimize recovery strategies.